ASSIGNMENT OF RESPONSIBILITY AND WORK BEHAVIOUR IN MANUFACTURING ORGANISATIONS IN NORTH CENTRAL, NIGERIA - Kayode, Olumuyiwa Ebenezer (African Journal of Social and Behavioural Sciences, 2025)
Many manufacturing organisations face significant challenges related to the assignment of responsibility and its impact on work behaviour. These issues persist despite the critical role that clear responsibility delineation plays in enhancing productivity and employee satisfaction. This study examines how responsibility assignment influences work behaviour in North Central Nigeria's manufacturing sector, providing insights into autonomy's role in enhancing employee engagement and performance. A diverse sample of employees and management staff participated in the study. The theoretical foundation for this research is the Job Characteristics Theory. A cross-sectional descriptive survey was conducted to gather responses from employees focusing on how the assignment of responsibility influences workplace behaviour. Data were analysed using descriptive statistics, such as; frequency percentages and distribution tables, and inferential statistics, specifically chi-square tests, to examine the relationships between dependent and independent variables. The results indicate that proper delegation of responsibilities positively impacts work behaviour by enhancing employees' feelings of ownership, accountability, and engagement. Additionally, the findings show that unfavourable working conditions will likely lead to a decline in job performance. Implications for management include the need for structured responsibility frameworks, regular feedback mechanisms, and cultural sensitivity in the design and implementation of responsibility assignments. This study shows that the role of assignment of responsibility and work behaviour is essential for organisational prosperity. It ends with recommendations for organisations to provide sufficient autonomy and assign responsibilities that stimulate job performance.